Predictors of International Students’ Socio-Cultural Adjustment - (:unkn) unknown (My University, 2016)
International students’ well-being and their adjustment have gained interest from researchers in different areas, including educational psychology, social psychology and counseling psychology. By using the social cognitive model, this study focused on finding the relationships among English fluency, social self-efficacy, cultural values, perceived social support, perceived discrimination and conflict handling styles and how they affect international students’ sociocultural adjustment. A hierarchical regression model found that international students with high social self-efficacy have less socio-cultural adaptation difficulties when they perceived low discrimination. However, when these students perceived high discrimination, they experienced higher socio-cultural adaptation difficulties. International students who valued openness to change reported lower socio-cultural adaptation difficulties. While international students’ English fluency in writing and speaking influenced their social self-efficacy, English fluency as a whole did not influence socio-cultural adaptation after factors such as perceived discrimination, social support, social self-efficacy and values were controlled. Finally, international students using dominate conflict handling style and international students using avoidance conflict handling style showed differences in their conservation value, but different conflict handling styles did not influence the relationship between English fluency and social self-efficacy. Implications are discussed. Limitations of the study and suggestions for future studies are provided.
Keywords: Discrimination; International Student; Social Self-Efficacy; Social Support; Socio-Cultural Adjustment